The role of TGF-β1 in chronic multilobar segmental bronchial stenosis and advances in targeted drug research - Wu, Mingjun; Yang, Qian; Xie, Youcheng; Hou, Yan; Xue, Qingliang (Frontiers in Pharmacology, 2025)
Chronic multilobar segmental bronchial stenosis (CMBS) is a chronic inflammatory airway disease characterized by stenosis across multiple lobar and segmental bronchi, primarily diagnosed via bronchoscopy. Epidemiologically, its prevalence exhibits significant regional variation, ranging from 0.1% to 22.5%, with higher rates observed in developing countries, rural populations, women, and individuals with a history of tuberculosis. Clinically, CMBS manifests as progressive dyspnea, chronic cough, recurrent pulmonary infections, and obstructive ventilatory dysfunction that is typically poorly responsive to bronchodilators. Radiologically, high-resolution computed tomography (HRCT) reveals characteristic bronchial wall thickening, luminal narrowing, and often associated mediastinal or peribronchial calcified lymph nodes. Long-term exposure to biomass fuel smoke (e.g., from wood or coal combustion), is established as a major etiological factor. Other significant risk factors include prior tuberculosis infection, and occupational exposures to inhalable irritants like silica dust in mining or textile workers. Despite its considerable global disease burden, the precise pathogenesis remains elusive. Research has identified transforming growth factor-β1 (TGF-β1) as a pivotal regulator of airway remodeling in various chronic respiratory diseases, such as asthma and chronic obstructive pulmonary disease (COPD). Notably, animal models of chronic biomass smoke exposure demonstrate a significant correlation between upregulated TGF-β1 expression and a distinct airway remodeling phenotype, suggesting its potential involvement in the pathological progression of CMBS. Accumulating evidence indicates that TGF-β1 mediates airway remodeling through multiple intricate mechanisms, including immune dysregulation, fibroblast activation and proliferation, aberrant extracellular matrix (ECM) deposition, epithelial-mesenchymal transition (EMT), and pathological vascular remodeling. In recent years, groundbreaking progress has been made in research on therapeutics targeting the TGF-β1 signaling pathway, including monoclonal antibodies (e.g., Fresolimumab), small molecule kinase inhibitors (e.g., Galunisertib, TEW-7197), and novel targeted delivery systems. This review systematically summarizes the molecular mechanisms of TGF-β1 in CMBS airway remodeling and the advances in the development of targeted drugs. Furthermore, it proposes future research directions focused on CMBS-specific applications, such as validating these therapeutics in preclinical CMBS models, developing inhaled formulations for localized delivery, establishing biomarker-driven patient stratification, and exploring combination therapies with anti-fibrotic agents. This aims to provide a comprehensive theoretical foundation for elucidating the disease’s pathology and developing novel, precise diagnostic and therapeutic strategies for CMBS.